Inflammasome Activation Triggers Blood Clotting and Host Death through Pyroptosis - Wu, Congqing; Lu, Wei; Zhang, Yan; Zhang, Guoying; Shi, Xuyan; Hisada, Yohei; Grover, Steven P.; Zhang, Xinyi; Li, Lan; Xiang, Binggang; Shi, Jumei; Li, Xiang-An; et al. (Immunity (Cambridge, Mass.), 2019)
Inflammasome activation and subsequent pyroptosis are critical defense mechanisms against microbes. However, overactivation of inflammasome leads to death of the host. Although recent studies have uncovered the mechanism of pyroptosis following inflammasome activation, how pyroptotic cell death drives pathogenesis, eventually leading to death of the host, is unknown. Here, we identified inflammasome activation as a trigger for blood clotting through pyroptosis. We have shown that canonical inflammasome activation by the conserved type III secretion system (T3SS) rod proteins from Gram-negative bacteria or noncanonical inflammasome activation by lipopolysaccharide (LPS) induced systemic blood clotting and massive thrombosis in tissues. Following inflammasome activation, pyroptotic macrophages released tissue factor (TF), an essential initiator of coagulation cascades. Genetic or pharmacological inhibition of TF abolishes inflammasome-mediated blood clotting and protects against death. Our data reveal that blood clotting is the major cause of host death following inflammasome activation and demonstrate that inflammasome bridges inflammation with thrombosis. [Display omitted] •Canonical or noncanonical inflammasome activation leads to blood clotting•Inflammasome activation induces blood clotting through pyroptosis•Tissue factor released from pyroptotic macrophages drives blood blotting•Interfering tissue factor prevents pyroptosis-induced lethality Overactivation of inflammasome leads to death of the host. Wu and colleagues demonstrate that activation of coagulation is responsible for inflammasome activation-induced death.